Beyond the BET Family: Targeting CBP/p300 with 4‐Acyl Pyrroles. (7th September 2017) - Hügle, Martin; Lucas, Xavier; Ostrovskyi, Dmytro; Regenass, Pierre; Gerhardt, Stefan; Einsle, Oliver; Hau, Mirjam; Jung, Manfred; Breit, Bernhard; Günther, Stefan; Wohlwend, Daniel
Abstract: Bromodomain and extra‐terminal domain (BET) inhibitors are widely used both as chemical tools to study the biological role of their targets in living organisms and as candidates for drug development against several cancer variants and human disorders. However, non‐BET bromodomains such as those in p300 and CBP are less studied. XDM‐CBP is a highly potent and selective inhibitor for the bromodomains of CBP and p300 derived from a pan‐selective BET BRD‐binding fragment. Along with X‐ray crystal‐structure analysis and thermodynamic profiling, XDM‐CBP was used in screenings of several cancer cell lines in vitro to study its inhibitory potential on cancer cell proliferation. XDM‐CBP is demonstrated to be a potent and selective CBP/p300 inhibitor that acts on specific cancer cell lines, in particular malignant melanoma, breast cancer, and leukemia. Abstract : XDM‐CBP ist ein hoch wirksamer und selektiver Inhibitor der Bromodomänen (BRDs) von CBP und p300, der sich von einem pan‐selektiven BET („bromodomain and extra‐terminal domain") bindenden Fragment ableitet. Nach Röntgenstruktur‐ und thermodynamischen Analysen wurde XDM‐CBP in In‐vitro‐Screenings gegen verschiedene Krebszelllinien auf eine mögliche Inhibition der Krebszellproliferation hin untersucht.